Clostridioides difficile Infection in Liver Cirrhosis: A Concise Review. (7th June 2022) - Liu, Yuanbin; Chen, Mingkai
Abstract : Clostridium difficile is a Gram-positive bacillus with fecal-oral transmission and is currently one of the most common nosocomial infections worldwide, which was renamed Clostridioides difficile in 2016. Clostridioides difficile infection (CDI) is a prevalent infection in cirrhosis and negatively affects prognosis. This study aimed to provide a concise review with clinical practice implications. The prevalence of CDI in cirrhotic patients increases, while the associated mortality decreases. Multiple groups of risk factors increase the likelihood of CDI in patients with cirrhosis, such as antibiotic use, the severity of cirrhosis, some comorbidities, and demographic aspects. Treatment in the general population is currently described in the latest guidelines. In patients with cirrhosis, rifaximin and lactulose have been shown to reduce CDI risk due to their modulatory effects on the intestinal flora, although conflicting results exist. Fecal microbiota transplantation (FMT) as a treatment for the second or subsequent CDI recurrences has demonstrated a good safety and efficacy in cirrhosis and CDI. Future validation in more prospective studies is needed. Screening of asymptomatic patients appears to be discouraged for the prevention currently, with strict hand hygiene and cleaning of the ward and medical equipment surfaces being the cornerstone of minimizing transmission.